Profitability and technical efficiency of soybean production in northern Nigeria - Ugbabe, O.O.; Abdoulaye, Tahirou; Kamara, A.; Mbaval, J.; Oyinbo, O. (2017)
The International Institute of Tropical Agriculture and collaborating partners have been introducing and disseminating short season soybean varieties among farm households in the Sudan savannas of Northern Nigeria since 2008. Yet, there is no empirical information on the profitability and technical efficiency of soybean production. This study estimated the profitability and efficiency of production of the early maturing soybean. Nine hundred soybean farming households in thirty communities from three Local Government Areas (LGAs) in Kano State were sampled for the study. Partial budget technique and stochastic frontier production function were used to analyze the data elicited from the sampled farm households. Results from the study established the profitability of soybean production in all the three LGAs of Kano State. The highest profit of N178,613/ha and returns per naira invested of 2.5 respectively was earned by the soybvean producing households of Dawakin-Tofa LGA. Net profit was N157,261 in Shanono with a returns of 1.75 per naira invested. In Bunkure, net benefit was N143,342 with returns of 1.66 per Naira invested. The mean technical efficiency was highest for the Dawakin-Tofa LGA soybean growing households (87%), followed by Bunkure LGA (68%), and Shanono LGA (59%). This result implies that given the current level of resources available to the soybean producing households, they can increase their soybean output in the short run by a margin 13%, 32% and 41% in Dawakin-Tofa, Bunkure and Shanono LGAs respectively through efficient utilization of their available resources. FArmer-specific efficiency factors, which comprise age, education, access to credit, extension contact and farming experience, were found to be the significant factors that account for the observed variation in efficiency among the farmers in the 3 LGAs. It was recommended that the soybean farmers through the assistance of extension agents should be encouraged to adhere strictly to the recommended soybean production practices towards ensuring efficient utilization of their available resources so that they can improve their technical efficiency and increase their profit level towards enhancing their household food security.